PERENCANAAN PEMBANGUNAN PASAR DENGAN FASILITAS RAMAH LINGKUNGAN DI KELURAHAN TALANG PUTRI - Aditia, M.; Rosyad, Farlin (Ensiklopedia Research and Community Service Review, 2025)
This research discusses planning for market development with environmentally friendly facilities in Talang Putri Village. The aim of this research is to design a sustainable market by considering environmental, social and economic aspects. The methods used include collecting data related to structural strength, selecting environmentally friendly materials, utility systems, environmental studies, budget plans (RAB), and making technical drawings. The research results show that this market planning includes several main components: (1) efficient design and spatial layout with product-based zoning, (2) use of environmentally friendly materials such as environmentally friendly concrete, light steel, and recycled paving blocks, (3) integrated waste management system, and (4) utilization of renewable energy through solar panels and energy-saving LED lights. This market is designed with sustainability aspects in mind, including waste management systems, use of renewable energy, and selection of environmentally friendly materials. In conclusion, this market development planning does not only focus on economic functions, but also considers environmental and social impacts, so that it can become a model of sustainable market development that supports improving the quality of life of the community.Keywords: Land use, Google Earth, remote sensing, image interpretation,    Kalidoni Distric